Risk of Handling Paper Currency in Circulation Chances of Potential Bacterial Transmittance - Lamichhane, Janardan; Adhikary, Satish; Gautam, Prson; Maharjan, Rajani; Dhakal, Bishal (Nepal Journal of Science and Technology, 2010)
butchers, food sellers, and banks) where paper currency is widely used. The currencies used by public transport in Nepal (micro-buses) were found to be extremely contaminated with various pathogenic bacteria followed by the currency used by butchers and food sellers. These microorganisms could be one of the major causes of widely transmitting diseases in Nepal. Eight different pathogenic bacteria were isolated that are the known to be involved in transmitting various diseases in Nepal. A lot of people loss their life every year in Nepal due to the transmittance of diseases by these kind of bacteria. Use of paper money could be one of the major sources of transmittance of such diseases in Nepal that provides platform for the growth of such bacteria. Public awareness of using paper currency in circulation became essential for the safety in human health. Key words: Escherichia coli; Infections; Pathogens; Staphylococcus aureus; Salmonella choleraesius DOI: http://dx.doi.org/10.3126/njst.v10i0.2952 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 161-166